Miejsce językoznawstwa w?badaniach translatologicznych = Linguistics in Translatological Research - Sławkowa, Ewa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article argues that the evolution of linguistics has provided translatology with two main methodological paradigms - structuralist and congitivist-anthropological. The former contributed to translatology the view of the systemic structure of languages and hence formulated a concept of translation based on the concepts of objectivism and strict and rigorous scientific procedures. E. Nida`s theory of equivalence as well as I. Evan-Zohar`s theory of polisystems resulted from the structuralist inspiration.
Keywords: ekwiwalencja formalna; ekwiwalencja dynamiczna; dominanta semantyczna; polisystem; kod kulturowy; dynamic equivalence; formal equivalence; semantic dominant; cultural code